1)wykonaj redukcje wyrazow podobnych.
a)x+y+x+y+x+y-x-y
b)x²-y+x-y-x²-x²+x
c)3x-2y+5x-6y-x
d)0,3a+0,4b-0,6a+2/5b
e)8z-1/4z-1/8z+3/4z+z
f)2ab-2b+4ab-5a-6b



2)wykonaj redukcje wyrazow podobnych.
a)3xy+4x-5xy+10-2x+2xy
b)1,5x²-0,2y²+0,5x²+0,8y²
c)-0,25xy+5+4/5xz-0,5-3/4xy
d)-x²-x+4x-5x²+0,8y²
e)-1/8x²-8z+0,125x²+8z+0,8x²y-3-4/5x²y



3) usun nawiasy i wykonaj redukcje wyrazow podobnych.
a) (a+b)+(2a-b)
b)2x+(3y-2z)+(3z-2x)
c)-5ab+(bc-2ab)+4cb
d)(5xyz-2xz)+(4zx-7zyx)
e)(m+n)-(2m+3n)
f)(2xy+4y²)-(3yx-2y²)
g)3abc-(2cab+5bac)
h)10x²y-(5xy²-8x²y)

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-01T17:55:33+01:00
1)wykonaj redukcje wyrazow podobnych.
a)x+y+x+y+x+y-x-y = 2x+2y
b)x²-y+x-y-x²-x²+x = -x²-2y+2x
c)3x-2y+5x-6y-x = 7x-8y
d)0,3a+0,4b-0,6a+2/5b = -0,3a+0,8b
e)8z-1/4z-1/8z+3/4z+z = 9,375 z
f)2ab-2b+4ab-5a-6b = 6ab-8b-5a



2)wykonaj redukcje wyrazow podobnych.
a)3xy+4x-5xy+10-2x+2xy = 2x+10
b)1,5x²-0,2y²+0,5x²+0,8y² = 2x² +0,6y²
c)-0,25xy+5+4/5xz-0,5-3/4xy = -⁷/₁₀ xy+4,5
d)-x²-x+4x-5x²+0,8y² = -6x²+3x+0,8y²
e)-1/8x²-8z+0,125x²+8z+0,8x²y-3-4/5x²y = -3



3) usun nawiasy i wykonaj redukcje wyrazow podobnych.
a) (a+b)+(2a-b) = a+b+2a-b = 3a
b)2x+(3y-2z)+(3z-2x) = 2x+3y-2z+3z-2x = 3y+z
c)-5ab+(bc-2ab)+4cb = -5ab+bc-2ab+4cb = -7ab+5bc
d)(5xyz-2xz)+(4zx-7zyx) = 5xyz-2xz+4zx-7zyx = -2xyz+2xz
e)(m+n)-(2m+3n) = m+n-2m-3n = -m-2n
f)(2xy+4y²)-(3yx-2y²) = 2xy+4y² -3yx+2y² = -xy+6y²
g)3abc-(2cab+5bac) = 3abc - 2cab -5bca = -4abc
h)10x²y-(5xy²-8x²y) = 10x²y-5xy²+8x²y = 18x²y -5xy²